Attitudes of Medical Doctors towards Conflicting Situations in Forensic Case Declaration - Can, İsmail Özgür; Direk, Neşe; Özdemir, Mehmet Hakan (The Bulletin of Legal Medicine, 2018)
Introduction: Double liability of health professionals occurs in situations in which decleration of forensic case is required. Medical doctors may experience conflicts between legislation and ethical principles. In this study, we aimed to explore the level of knowledge about forensic case declaration of medical doctors working at the XXX Medical Center. Also, we aimed to determine their attitudes and behaviours towards the situations in which ethical principles and legislation conflict is present to their knowledge.  Methods: We used a 22-item questionnaire including items to evaluate the definition of a forensic case, liability of declaration of forensic case, knowledge about legislation and ethical principles, attitudes and behaviour towards the conflicting situations. In total, 106 medical doctors were evaluated.  Results: Sixty-two percent of medical doctors follow legislation and 35% of them follow ethical principles when they face with conflicting situations.Discussion: We discussed situations in which medical and ethical principles contradict and agree with legislation. We believe that such discussion would be helpful to attitude changes in conflicting situations.
Keywords: forensic science; forensiz case; declaration of forensic case; double liability; medical ethics